2021
DOI: 10.3390/diagnostics11050756
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and Magnetic Resonance Imaging of Rectal Cancer: From Engineering to Clinical Practice

Abstract: While cross-sectional imaging has seen continuous progress and plays an undiscussed pivotal role in the diagnostic management and treatment planning of patients with rectal cancer, a largely unmet need remains for improved staging accuracy, assessment of treatment response and prediction of individual patient outcome. Moreover, the increasing availability of target therapies has called for developing reliable diagnostic tools for identifying potential responders and optimizing overall treatment strategy on a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…The recent development of TA and radiomics-based image analysis have introduced new predictive modelling techniques and offered promising insights for quantitative imaging characterization of rectal cancer, when compared to the mere volumetric assessment [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…The recent development of TA and radiomics-based image analysis have introduced new predictive modelling techniques and offered promising insights for quantitative imaging characterization of rectal cancer, when compared to the mere volumetric assessment [ 139 ].…”
Section: Resultsmentioning
confidence: 99%
“…These radiomics features extracted from different MRI modalities could reflect tumor heterogeneity caused by variations in tumor intensity, cellularity, and vascularization, and a combination of radiomics features from multi-parametric MRI is likely to improve prognostication in comparison with radiomics features extracted from a single sequence. Although our results do not comprehensively identify the particular MRI sequences that provide the most relevant information for predicting the response to nCRT, radiomics analysis derived from multiparametric MRI clearly has the potential to provide added value to conventional MRI [ 34 , 35 ]. Nie et al found that radiomic features derived from T2WI, DWI, and CE-T1WI enhanced the predictive power of an artificial neural network classifier [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics aims to translate medical images into quantitative data, defined as biomarkers, which may reveal a deeper level of detail than that, which is accessible to the unaided human eye, so as to quantify tumor phenotypes, which could aid in clinical decision-making ( 14 ).Radiomics may provide quantitative and objective support for decisions surrounding cancer detection and treatment ( 15 , 16 ).TA belongs to radiomics. TA by mathematical methods of quantitative imaging image pixel gray level statistics and spatial distribution and structure information, to extract the texture feature which cannot be identified by the naked eye, revealing the heterogeneity of tumor histologic features and certain genes, and by using the quantitative information of the differential diagnosis of the disease, grading, classification and evaluation of curative effect ( 7 , 17 ).…”
Section: Discussionmentioning
confidence: 99%